KERALA POPULATION AGEING FAST – SOME REFLECTIONS - Sini Thomas M. (MIRROR, 2018)
Social security to elderly is not charity but their basic human right. The elderly population (60+) in India is a fast growing phenomenon. India’s population grew by 17.6 per cent during the past decade; Kerala’s growth rate was merely 4.6 per cent. People above 60 constitute 13 per cent of the state’s population of 3.34 crore compared to the national figure of 8.2 per cent, according to the 2011 Census. “The famed Kerala model of development with emphasis on public health gave people longer lives. But it has failed in providing quality lives,” says demographer S. Irudaya Rajan. The proportion of the elderly dependent population in the state is 57.8 per cent, and 35.1 per cent of the aged possess no property. At Rs 7,311 crore, the annual outgoing from the exchequer for pensions is more than 35 per cent of the total tax receipts. This paper focuses on the demographic trends and also the magnitude of ageing in state as well as the national level.